2023
DOI: 10.1002/pssa.202300113
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study of the Excitonic Structure in Monolayer MoS2 under Multivariate Physical and Chemical Stimuli

Abstract: Photoluminescence (PL) spectroscopy has proven to provide deep insights into the optoelectronic properties of monolayer . Herein, a corresponding study is conducted on the excitonic properties of mechanically exfoliated monolayer under multivariate physical and chemical stimuli. Specifically, midgap exciton states that originate from lattice defects are characterized and they are compared to existing models. Through statistical data analyses of substrate‐, temperature‐, and laser‐power‐dependent measurements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Further, the total PL intensity from the samples increases as the temperature is lowered, due to reduced phonon interactions (reduced scattering out of the light cone) and nonradiative recombination (carrier scattering) [29]. The blueshift in peak position with the temperature is due to an increase in the bandgap, as observed for most semiconductors [30][31][32]. For all samples, the linewidth of the A-exciton reduces with the temperature due to the reduced phonon-induced homogeneous broadening.…”
Section: Resultsmentioning
confidence: 79%
“…Further, the total PL intensity from the samples increases as the temperature is lowered, due to reduced phonon interactions (reduced scattering out of the light cone) and nonradiative recombination (carrier scattering) [29]. The blueshift in peak position with the temperature is due to an increase in the bandgap, as observed for most semiconductors [30][31][32]. For all samples, the linewidth of the A-exciton reduces with the temperature due to the reduced phonon-induced homogeneous broadening.…”
Section: Resultsmentioning
confidence: 79%
“…Here, the dots correspond to the measured data, and the solid lines are the total fitted curves, with filled curves representing the individual excitonic components. We use the PLinterafit Python package , to fit Voigt functions to our measured data and statistically analyze the quality of our fit. Based on our analysis with two and three Voigt functions, we concluded that we cannot describe the PL measurements with acceptable goodness-of-fit values using only Voigt functions.…”
mentioning
confidence: 99%
“…Here, the dots correspond to the measured data, and the solid lines are the total fitted curves, with filled curves representing the individual excitonic components. We use the PLinterafit Python package 40,41 to fit Normalized difference reflection (DR) spectra from measurements (dots) and normalized cross sections from simulations (solid lines). The scattering (σ sca ) and absorption (σ abs ) cross sections of the hybrid system are shown as black and red solid lines, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation